Antiplatelet drug interactions with proton pump inhibitors. (February 2014) - Scott, Stuart A; Owusu Obeng, Aniwaa; Hulot, Jean-Sébastien
<x xml:space="preserve">Abstract</x> Introduction: Non-aspirin antiplatelet agents (e.g., clopidogrel, prasugrel, ticagrelor) are commonly prescribed for the prevention of recurrent cardiovascular events among patients with acute coronary syndromes (ACS) and/or those undergoing percutaneous coronary intervention (PCI). In addition, combination therapy with proton pump inhibitors (PPIs) is often recommended to attenuate gastrointestinal bleeding risk, particularly during dual antiplatelet therapy (DAPT) with clopidogrel and aspirin. Importantly, a pharmacological interaction between clopidogrel and some PPIs has been proposed based on mutual CYP450-dependent metabolism, but available evidence is inconsistent. Areas covered: This article provides an overview of the currently approved antiplatelet agents and PPIs, including their metabolic pathways. Additionally, the CYP450 isoenzyme at the center of the drug interaction, CYP2C19, is described in detail, and the available evidence on both the potential pharmacological interaction and influence on clinical outcomes are summarized and evaluated. Expert opinion: Although concomitant DAPT and PPI use reduces clopidogrel active metabolite levels and ex vivo-measured platelet inhibition, the influence of the drug interaction on clinical outcomes has been conflicting and largely reported from non-randomized observational studies. Despite this inconsistency, a clinically important interaction cannot be definitively excluded, particularly among patient subgroups with higher overall cardiovascular risk and potentially among CYP2C19 loss-of-function allele carriers.